PENERAPAN PROGRAM LANGIT BIRU TERHADAP PENURUNAN PENYAKIT ISPA DI KOTA KENDARI - Osu Oheoputra Husen (Jurnal Akrab Juara, 2019)
Transportation is an important activity in the lives of Indonesian people. However, in the implementation of transortions it has a negative impact on the environment such as air pollution. The air pollution caused by pollutants has an impact on public health, ARI is a respiratory disease that is often experienced by urban communities. The Blue Sky program is an effort to reduce air pollution from the transportation sector that has been launched since 1996. The results of the Langit Biru program on reducing respiratory distress cases have not yet been felt, various obstacles in this program are still being obtained. In fact, several studies in other countries have shown that air pollution control can contribute significantly to decreasing cases of respiratory disease. Therefore, in order to realize safe air quality for health, greater support and roles are needed from the government, program implementers, and the community.